Equity financing and innovation: Is Europe different from the United States? - Martinsson, Gustav (Journal of Banking & Finance, 2010)
During the mid and late 1990s young, high-tech firms in the US experienced a supply shift in both internal and external equity fueling a finance-driven boom in corporate R&D. This paper examines whether R&D spending in Europe in a similar way was sensitive to fluctuations in the supply of internal and external equity during the late 1990s and early 2000s. I conjecture that UK and Continental Europe, due to their different financial systems, differ in terms of equity supply. I estimate dynamic R&D regression models for UK and Continental European high-tech firms separately and find significant joint cash-flow effects for newly listed firms in both samples. However, only new firms in the UK experienced a joint external equity effect as well. The findings of this paper suggest a channel through which market-based financial systems outperform the bank-based economies of Continental Europe.